Improving Children's Cognitive Intelligence Through Literacy Management - Umiarso Umiarso; Hasan Baharun; Zamroni Zamroni; Fathor Rozi; Nurul Hidayati (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Cognitive intelligence has a vital role in children's growth and development to solve remembering, logical thinking, and symbolic thinking activities. This study aim to explore how the implementation of in improving early childhood cognitive intelligence in RA Tania, Paiton, Probolinggo?. This research uses a qualitative case study approach. Researchers conducted observations and interviews with principals, teachers, students, and guardians of students. The data analysis technique is carried out in stages, including data presentation, data reduction, and concluding. The results showed that literacy management in improving early childhood cognitive intelligence was carried out through; identification of needs, implementation of literacy management, evaluation, and a tiered plan. This study implies that literacy management can increase interest in reading and writing and an understanding of simple problem-solving in early childhood